What qualities should a multicultural teacher have? - Balık, Cemile; Şahin, Harun (Tokat Gaziosmanpaşa Üniversitesi, 2026)
The current study aims to identify the characteristics that a multicultural teacher should possess based on the perspectives of in-service and pre-service teachers. The study was conducted within the framework of a basic qualitative research design involving in-service and pre-service teachers as participants. Data were collected through an open-ended questionnaire and were analyzed by using content analysis. The findings indicate that both groups expressed largely similar views regarding multicultural teacher characteristics in terms of values, skills, competencies, and conceptual biases. However, the in-service teachers placed greater emphasis on personal development compared to the pre-service teachers. Among the identified dimensions, values emerged as the most frequently emphasized theme, while empathy and communication skills were highlighted as essential skills for multicultural teaching. The in-service teachers emphasized technology use as an important professional competency, whereas the pre-service teachers focused more on cultural knowledge and inclusivity. The higher expression of conceptual biases among the pre-service teachers was associated with their limited classroom experience. Overall, the findings suggest that the mere transmission of knowledge is insufficient in teacher education; rather, teacher preparation should incorporate practical experiences and field-based opportunities that foster empathy, communication skills, technology use, and personal development. By examining multicultural teacher characteristics through the subjective evaluations of professionals and future teachers, the current study offers a distinct contribution that complements existing theoretical and quantitative research in the field.
Keywords: Multiculturalism; Multicultural Teacher; Multicultural Education; Multicultural Personality Traits